(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Idioms serve a pivotal function in communication within diverse linguistic environments. This article delves into the attributes of idiomatic expressions and their paramount significance in facilitating efficient communication. It scrutinizes the assorted categories of idioms, delineates their structural attributes, and elucidates their functions in discourse. Through a meticulous examination, this research endeavor seeks to furnish a comprehensive understanding of the pivotal role of idioms in augmenting linguistic competency and conveying cultural subtleties.